Surface Plasmon Resonance Based Sensor for Amaranth Detection With Molecularly Imprinted Nanoparticles - Fatma Ozge Ozgur; Duygu Çimen; Adil Denizli; Nilay Bereli (Photonic Sensors, 2023)
Abstract Amaranth imprinted nanoparticles were prepared by two-phase mini emulsion polymerization of hydroxyethyl methacrylate and ethylene glycol dimethacrylate using acrylamide and methacrylic acid as functional monomers. The amaranth non-imprinted nanoparticle was prepared with the same procedure without using amaranth. Amaranth imprinted and non-imprinted nanoparticles were attached on the chip surface modified with allyl mercaptan. The surfaces of the surface plasmon resonance (SPR) sensor were characterized by the ellipsometry, contact angle, and atomic force microscopy. Amaranth solutions with different concentrations (0.1mg/mL–150mg/mL) were prepared with the pH 7.4 phosphate buffer. The limit of detection and limit of quantification were 0.0180mg/mL and 0.06mg/mL, respectively. When the selectivity of the amaranth imprinted SPR sensor was compared with the competing molecules tartrazine and allura red, it was observed that the target molecule amaranth was 5.64 times and 5.18 times more selective than allura red and tartrazine, respectively. The liquid chromatography-mass spectrometry technique (LC-MS) was used for validation studies. According to the results obtained from both SPR sensor and LC-MS analyses, the amaranth recovery (%) from fruit juices was observed between 96% and 99%.